A National Survey of Dispensing Practice and Customer Knowledge on Antibiotic Use in Vietnam and the Implications - Thuy Thi Phuong Nguyen; Thang Xuan Do; Hoang Anh Nguyen; Cuc Thi Thu Nguyen; Johanna Catharina Meyer; Brian Godman; Phumzile Skosana; Binh Thanh Nguyen (MDPI AG, 2022)
Misconceptions and pressures have increased the sales of antibiotics without a prescription across countries. There are concerns with such practices in Vietnam given rising antimicrobial resistance rates. A national survey was conducted among 360 private drugstores located in nine provinces in Vietnam. Anonymous interviews were conducted with participants selected by convenience sampling. Subsequently, multivariable logistic regression analyses were undertaken evaluating the relationship between customer characteristics and antibiotic purchases. A total of 480 out of 1626 surveyed participants purchased antibiotics, 81.7% of which did not have a prescription, involving 29 different antibiotics. In 86.4% of these, participants were prescribed antibiotics by drug sellers. Most antibiotics were sold to treat respiratory tract infections (61.4%), with the 'Access' antibiotics (amoxicillin and cephalexin) being the most frequently sold. Only one-fifth of participants understood that they were breaking the law by purchasing antibiotics without a prescription. Participants purchasing antibiotics without a prescription had lower awareness concerning antibiotic laws and treatment duration (p < 0.05). Under 50% agreed to having a doctors' prescription in the future when purchasing antibiotics. Freelancer occupation (OR = 0.52, 95% CI = 0.83-0.96) and a lower educational level (OR = 0.49, 95% CI = 0.25-0.96) were factors related to purchasing antibiotics without a prescription. Overall, we recommend increasing fines and monitoring of drugs stores, greater promotion of the family doctor system as well as increasing media and educational campaigns to limit self-purchasing of antibiotics in Vietnam and reduce resistance.